Stability enhancement of DC power systems by VSM control strategy. (March 2021) - Yang, Yaqian; Xu, Jiazhu; Li, Chang; Dragicevic, Tomislav; Blaabjerg, Frede
Highlights: This article proposes a VSM control strategy to dampen oscillation of DC-side voltage, and to improve damping performance and inertia for DC power system. This paper proposed a new modeling method for identifying the dynamic interactions between multiple converters in a DC microgrid. Abstract: DC system is characterized by low inertia and weak damping, which leads to a couple of stability issues. This paper proposes a modeling method for analyzing the DC-side oscillations occurred in DC microgrid with taking multi-paralleled converters into account. A new modeling is developed for analysis of dynamic interaction between multiple power converters. Thus, it is found that dynamic interaction between multiple converters will result in the poorly-damped oscillation of DC voltage. Besides, the poorly-damped modes will aggravate the stability of DC system. To cope with this issue, a virtual synchronous machine (VSM) control approach is proposed to suppress the oscillation of DC voltage, strengthen inertia, and improve damping performance of DC microgrid. Besides, the controller tuning of the VSM has a large flexibility that it does not depend on the system parameters. Finally, the proposed conceives are demonstrated by simulations.